Structural aspects, thermal behavior, and stability of a self-assembled supramolecular polymer derived from flunixin-meglumine supramolecular adducts - Cassimiro, Douglas L. [UNESP]; Kobelnik, Marcelo [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Boralle, Nivaldo [UNESP] (Elsevier B.V., 2012)
Flunixin-meglumine, a potent non-steroidal anti-inflammatory drug (NSAID) and a cyclo-oxygenase inhibitor for Veterinary use, is a hydrogen-bonded supramolecular adduct. Two monotropically related crystalline modifications (Forms I and II) were observed for a flunixin-meglumine sample. During the melt of form I, flunixin-meglumine adducts self-assembled by hydrogen bonds involving the hydroxyl groups from meglumine, resulting in an amorphous rigid glassy supramolecular polymer, which showed a high molecular weight around 290 +/- 88 MDa and a glass transition around 49.5 degrees C. Both the adduct and the resulting supramolecular polymer were characterized by differential scanning calorimetry (DSC), nuclear magnetic resonance spectroscopy (NMR). Fourier transform-infrared spectroscopy (FT-IR), and weight-average molecular weight determination by light scattering. The chemical stability and morphological changes of the depolymerization process were also investigated for the supramolecular polymer, by DSC and scanning electron microscopy (SEM), respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Flunixin-meglumine; Supramolecular adduct; Self-assembly; Hydrogen bond; Supramolecular polymer; Stability